PENGEMBANGAN E-MODUL UNTUK MENINGKATKAN SPATIAL VISUALIZATION INTELLIGENCE PADA MATERI PROYEKSI ORTOGONAL DI SMK NEGERI 1 SIDOARJO - Chotmi Syayidah Maulidya; Hendra Wahyu Cahyaka (Jurnal Kajian Pendidikan Teknik Bangunan, 2023)
Many students who lacked spatial visualization intelligence or spatial-visual skills found it difficult to analyze, comprehend, and interpret engineering drawings, especially when competing with DPIB skills. However, this ability can be enhanced through precise educational approaches, such as using media that aligns with the subject's concept, like e-modules. The objective of this study was to gain insights into two things: (1) the effectiveness of e-modules in enhacing spatial visualization intelligence, as assessed through student assesment in orthogonal projection material, and (2) student feedback on the e-module for learning orthogonal projection material.The study employed the RnD ASSURE research method, encompassing six steps: analyze learners; state objectives; select methods, media, and materials; utilize media and materials; require learner's participation; and evaluate and revise. The product trial phase involved a quasi-experimental pretest-posttest control group design conducted on X-DPIB students at SMK Negeri 1 Sidoarjo. The experimental group, utilizing the e-module, achieved an average n-gain value of 0.62, categorized as